PENGARUH PENDEKATAN KONTEKSTUAL DENGAN STRATEGI REACT TERHADAP HASIL BELAJAR KOGNITIF MATERI BANGUN RUANG PADA SISWA KELAS V SDN 1 GONDANG - Dwi Cahyani; Rohmatus Syafi’ah (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The lack of the cognitive learning on the material of building is background of this research. It is proved of almost students that getting of lower score in criteria completeness of minimum (KKM). One of alternative solution from this problem is apply of contextual approach with REACT strategy. The purpose of this research to describe there is any influence between contextual approach and REACT strategy for the result of lesson special on building material. This research is quantitative research design with quasi experimental. The research show that there is any influence between contextual approach and REACT strategy for the cognitive learning. The analysis of data t-test show that score Sig.(2-tailed) < 0,05 is 0,000 < 0,05.Keywords: contextual approach, react strategy, cognitive learning, building space